2018
DOI: 10.1097/njh.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Development of the End-of-Life Care Nursing Attitude Scale for Japanese Geriatrics

Abstract: This study aimed to develop an end-of-life (EOL) care nursing attitude scale for Japanese geriatric nurses (ELNAS-JG). The items of the ELNAS-JG were developed to cover important topics related to EOL care (eg, motivation for providing EOL care, pain and symptom management, and decision-making support care for older adults). Participants were 1663 nurses employed in 32 institutions across Japan. Of these, 1298 participants were analyzed. An exploratory factor analysis of the 26 scale items revealed a 3-factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The ELNAS-JG consists of 26 items rated on a 5-point Likert scale, from “1 = strongly disagree” to “5 = strongly agree”; higher scores indicate more positive attitudes toward end-of-life care. The validity and reliability (Cronbach’s α = 0.96) of the ELNAS-JG were confirmed in a previous study [ 40 ]. Reliability was also confirmed using data from the present study (e.g., α ranged from 0.95 to 0.97 for various time points).…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The ELNAS-JG consists of 26 items rated on a 5-point Likert scale, from “1 = strongly disagree” to “5 = strongly agree”; higher scores indicate more positive attitudes toward end-of-life care. The validity and reliability (Cronbach’s α = 0.96) of the ELNAS-JG were confirmed in a previous study [ 40 ]. Reliability was also confirmed using data from the present study (e.g., α ranged from 0.95 to 0.97 for various time points).…”
Section: Methodssupporting
confidence: 74%
“…Attitude toward end-of-life care . Staff’s attitude toward end-of-life care for older adults was measured using an end-of-life care nursing attitude scale for Japanese geriatric nurses (ELNAS-JG), which measures attitudes toward end-of-life care for older adults in any end-of-life setting [ 40 ]. The ELNAS-JG consists of 26 items rated on a 5-point Likert scale, from “1 = strongly disagree” to “5 = strongly agree”; higher scores indicate more positive attitudes toward end-of-life care.…”
Section: Methodsmentioning
confidence: 99%
“…The original ELNAS‐JG includes 26 items rating nurses’ attitudes for EOL care on a 5‐point Likert scale from 1 (“strongly disagree”) to 5 (“strongly agree”) with total score from 26 to 130; higher scores indicate better attitudes about EOL care (Cronbach's α = 0.95, intraclass correlation coefficient = 0.83). This scale has good internal consistency, test–retest reliability, content validity, known‐groups validity and construct validity (Okumura‐Hiroshige et al, ). The Cronbach's α was 0.96.…”
Section: The Studymentioning
confidence: 99%
“…Specialised education can improve nurses’ advanced assessment and care skills; poor education hinders appropriate EOL nursing care (Anstey, Powell, Coles, Hale, & Gould, ; Teixeira et al, ). Palliative care is lacking in nursing curricula (Paice et al, ); 75% of nurses working in Japanese EOL facilities for older adults reported never receiving EOL care education (Okumura‐Hiroshige et al, ). Previous studies on EOL care focused on specialised EOL care education, mainly for cancer (Bakitas et al, ; Bridges, Lucas, Wiseman, & Griffiths, ), advanced chronic diseases (Phongtankuel et al, ), and advanced dementia (Raymond et al, ).…”
Section: Introductionmentioning
confidence: 99%